The relationship of fine motor and gross motor skills to shooting performance in petanque athletes - Dessy Fitrianingtyas; Rivan Saghita Pratama; Benny Badaru (Sriwijaya Journal of Sport, 2026)
Research Problems: Motor skills are an important factor in supporting the performance of petanque athletes who demand accuracy. The fine motor plays a role in setting the right direction and throwing. Meanwhile, the gross motor plays a role in supporting the body in balance during the throwing process. The difference in the level of mastery of these two motor skills is thought to have a relationship with shooting results. Research Objectives: This research examines the relationship between fine motor and gross motor skills and the shooting results of petanque athletes. Methods: Correlational quantitative research involving petanque athletes in Semarang City. Research instruments include the Ball Throw & Catch Test, Nine Hole Peg Test, handgrip Dynamometer Test, and Shooting Station Test. Data were analyzed using Multiple Linear Regression Analysis, F Test, t Test, and Linear Regression Equation. Results: Simultaneously, fine motor and gross motor skills are significantly related to petanque shooting results. However, only the fine motor was significantly related. Conclusion: Fine motor skills, such as hand-eye coordination and finger control, play a major role in determining shooting throw accuracy. Meanwhile, gross motor skills, such as arm muscle strength, strongest leg stability, and core muscle strength, function as supporting factors in maintaining movement stability, but are not directly related to the athlete's shooting results. This research suggests the need to focus training on improving fine motor skills without neglecting general physical condition training to support athlete performance.